2021
DOI: 10.3389/fnins.2021.783624
|View full text |Cite
|
Sign up to set email alerts
|

Proteinopathies as Hallmarks of Impaired Gene Expression, Proteostasis and Mitochondrial Function in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset neurodegenerative disease characterized by progressive degeneration of upper and lower motor neurons. As with the majority of neurodegenerative diseases, the pathological hallmarks of ALS involve proteinopathies which lead to the formation of various polyubiquitylated protein aggregates in neurons and glia. ALS is a highly heterogeneous disease, with both familial and sporadic forms arising from the convergence of multiple disease mechanisms, many of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 178 publications
(206 reference statements)
0
14
0
1
Order By: Relevance
“…Many neurodegenerative diseases, including ALS, are considered proteinopathies, usually represented by the accumulation of protein aggregates [ 112 ]. Moreover, protein accumulation can be exploited for the discovery of new biomarkers, represented by evaluating the protein expression level in cerebrospinal fluid (CSF), plasma and PBMCs of ALS patients [ 42 ].…”
Section: Protein Expression In Pbmcs Of Als Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many neurodegenerative diseases, including ALS, are considered proteinopathies, usually represented by the accumulation of protein aggregates [ 112 ]. Moreover, protein accumulation can be exploited for the discovery of new biomarkers, represented by evaluating the protein expression level in cerebrospinal fluid (CSF), plasma and PBMCs of ALS patients [ 42 ].…”
Section: Protein Expression In Pbmcs Of Als Patientsmentioning
confidence: 99%
“…Many other proteins are involved in ALS [ 112 ]. For example, Kuźma-Kozakiewicz and colleagues focused their work on the expression of motor proteins involved in both the anterograde and the retrograde transport in PBMCs obtained from SALS patients, healthy control subjects and other neurological disease(s) patients [ 82 ].…”
Section: Protein Expression In Pbmcs Of Als Patientsmentioning
confidence: 99%
“…Accordingly, Singh et al identified similar mitochondrial dysfunction in both sALS and fALS human iPSCs-derived MNs [ 155 ]. However, differences in mitochondrial pathophysiology between sALS and fALS have been reported in other iPSCs models [ 107 , 150 , 151 ]. Choi et al investigated how the blockade of the PP1-DRP1 cascade effectively prevented mitochondrial defects and subsequent cell death in iPSC-derived human MNs [ 107 ].…”
Section: Mitochondrial Alterations In Sporadic Als Casesmentioning
confidence: 99%
“…In addition, much of the animal-model research focuses on mutations in the TARDBP transactive response DNA-binding protein gene (TDP-43) associated with approximately 5% of fALS cases [ 53 ], sarcoma fusion protein (fused in sarcoma (FUS)) and valosin-containing protein (VCP), due to its link to fALS and diseases of a similar nature [ 52 , 54 ].…”
Section: Pathogenesis Of Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In particular, alterations in the RNA recognition domain (RRM1) of TDP-43, induced by OS, can promote its aggregation and incorrect localization in the cytoplasm [ 60 ]. These abnormal protein aggregates are the most representative in ALS disease [ 54 , 61 , 62 ].…”
Section: Pathogenesis Of Amyotrophic Lateral Sclerosismentioning
confidence: 99%